2019
DOI: 10.1111/aogs.13724
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal and paternal height and weight on antenatal, perinatal and postnatal morphology in sex‐stratified analyses

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…These findings are similar to findings from the Generation R cohort of EFW in the Netherlands [33] and fetal biometric measurements in an Italian cohort [34] although another study from the UK also found maternal weight to have a stronger influence on birthweight, while maternal and paternal height had similar contributions [35]. The fact that maternal factors have a stronger influence on anthropometrics during fetal life compared to paternal factors has been hypothesized to be due to maternal preservation in conditions of constraint [36].…”
Section: Plos Onesupporting
confidence: 84%
“…These findings are similar to findings from the Generation R cohort of EFW in the Netherlands [33] and fetal biometric measurements in an Italian cohort [34] although another study from the UK also found maternal weight to have a stronger influence on birthweight, while maternal and paternal height had similar contributions [35]. The fact that maternal factors have a stronger influence on anthropometrics during fetal life compared to paternal factors has been hypothesized to be due to maternal preservation in conditions of constraint [36].…”
Section: Plos Onesupporting
confidence: 84%
“…In a study by Ghi et al ( 18 ), it was found that paternal height significantly affected fetal growth. On the contrary, a recent study by Skåren et al ( 19 ) revealed that it is maternal and not paternal factors that determine fetal growth in both genders. In the Intergrowth-21 study, fathers of infants born LGA were reported to be taller and heavier but it was the maternal BMI that had a dominant influence on LGA ( 20 ).…”
Section: Discussionmentioning
confidence: 87%
“…Where data for overall prevalence were not reported for n > 1000 participants (The Barwon Infant Study and NDSHS Cohort from 2010), these results were also excluded from the meta-analysis. Findings from 55 small cohort studies (<1000 participants) and/or case-control studies were reported by 59 publications, from which all relevant data were extracted and tabulated ( Supplementary Tables S8 and S9 ) [ 18 , 19 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ...…”
Section: Resultsmentioning
confidence: 99%